Stakeholders converge on integrated water storage in the Shashe Catchment - Sibanda, B. M. (International Water Management Institute, 2024)
A workshop on advancing integrated water storage in the Shashe Catchment, a sub-basin of the Limpopo Basin shared by Zimbabwe and Botswana, organized by Dabane and IWMI, demonstrated the transformative potential of collaborative efforts and innovative approaches in water storage.